Abolição sagrada para alguns - Graden, Dale T. (Afro-Ásia, 2022)
Resenha de: Needell, Jeffrey D. The Sacred Cause: The Abolitionist Movement, Afro-Brazilian Mobilization, and Imperial Politics in Rio de Janeiro. Stanford: Stanford University Press, 2020. 361 p.